Priority interventions for transformational change in the Sahel - Abberton, Michael T.; Abdoulaye, Tahirou; Ademonla, Djalal A; Asiedu, R.; Ayantunde, A.A.; Bayala, Jules; Cofie, Olufunke O.; Kane Potaka, Joanna; Zwart, Sander J.; Tabo, Ramadjita; Tenkouano, A.; Tepa-Yotto, Ghislain T.; et al. (Wageningen University & Research, 2021)
The Sahel region holds both challenges and opportunities for smallholder agriculture/agropastoralism. Market opportunities for food producers in the region have improved due to population growth, urbanization, income growth, dietary diversification and higher output prices. However, alongside land degradation and climate change, an increased dependence on dynamic food (and feed) value chains and on volatile markets indicates the need to address structural constraints such as limited access to high-potential agricultural innovations, ineffective policies, an underdeveloped business environment, poor infrastructure and processing facilities and a generally poor market infrastructure. To support the agricultural transformation required to meet these challenges, evidence needs to be provided to countries in the Sahel to enable them make informed decisions on policy reforms where and when needed. Several scaling approaches and technological solutions have been demonstrated to be effective and this document outlines proposed priority actions to achieve higher adoption of climate smart agriculture through Public-Private-Partnerships. A particular focus will be on the role of women and youth, both through improved household nutrition (and other attendant health and development benefits) and through improved job creation and wealth generation in various components of selected value chains. Meanwhile, the importance of improved agro-industrialization and trade for income generation and poverty reduction underscores the critical role of enhanced interaction with a vibrant private sector. This document presents some of the main routes by which R4D can contribute to agricultural transformation in the Sahel towards inclusive and sustainable economic growth, social development and resilience, including climate smart agricultural technologies appropriate to smallholder farming families. This will be achieved through a six pronged strategy: (i) Increasing the efficiency of tree, crop and livestock value chains, (ii) Empowerment and increased employment opportunities for women and youth in agriculture, (iii) Co-creation of context-specific, climate smart innovations to enhance climate resilience (iv) Value addition and improved nutrition, (v) Improved soil and water conservation and its utilization for production, (vi) Improved policy and institutional enabling environments.